Coexistence of Antiphospholipid Syndrome and Heparin-Induced Thrombocytopenia in a Patient with Recurrent Venous Thromboembolism - Samuel Adediran; Nicole Agostino (Case Reports in Hematology)
Heparin-induced thrombocytopenia (HIT) is a prothrombotic adverse drug reaction in which heparin forms complexes with platelet factor 4 forming neoantigens that are recognized by autoantibodies. Antiphospholipid syndrome (APS) is similar to HIT in that it is mediated by autoantibodies that are also prothrombotic. We present a case of rare coexistence of antiphospholipid antibody syndrome and heparin-induced thrombocytopenia.